Evidence based medicine applied to maternal and perinatal health - Távara Orosco, Luis (2015)
Evidence Based Medicine (EBM) is the practice of taking medical decisions by evaluating, identifying and implementing the most relevant information. It also means integrating individual clinical expertise with the best available scientific support from systematic research.